Possible Means of Electrostatic Propulsion According to the Mbelek–Lachièze-Rey Scalar-Tensor Theory of Gravitation - Minotti, Fernando Oscar (2018)
As was shown recently, the scalar-tensor theory of gravitation proposed by Mbelek and Lachièze-Rey allows for a possible explanation of the forces reported in asymmetric microwave cavities. We show here that the theory in its revised version predicts a much simpler way of producing thrust by electrostatic means. We here briefly present the equations and derivations indicating that a constant force is predicted for a spherical capacitor with an asymmetric mass distribution, kept at constant voltage. Apart form other practical implications, this particular prediction, and a complementary proposal in which the spherical capacitor takes the place of the large mass in a Cavendish-like experiment, provides an additional possibility of experimentally testing this particular scalar-tensor gravitational theory.